2014
DOI: 10.1016/j.jana.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Cessation Interventions in People Living With HIV Infection: A Systematic Review

Abstract: Tobacco smoking remains a prevalent behavior in people living with HIV infection (PLWHs) and is associated with impaired immune functioning, increased cardiovascular risk, and decreased response to antire-troviral therapy. This review presents a critique and synthesis of evidence on effective smoking-cessation interventions for PLWHs. A comprehensive search identified nine peer-reviewed intervention studies published between 1989 and 2012. The highest likelihood of smoking cessation (range of odds ratios 4.33–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 33 publications
(108 reference statements)
0
50
0
1
Order By: Relevance
“…Notably, HIV-infected individuals appear to smoke more than the general population. For example, studies in European and North American HIV-infected cohorts report a smoking prevalence ranging from 40% to >70%, two to three times that of the general population [5][6][7][8][9][10][11]. Notwithstanding the increased prevalence of smoking, HIV-infected smokers have a significant, albeit unexplained, increased mortality and decreased quality of life compared to HIV-uninfected smokers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, HIV-infected individuals appear to smoke more than the general population. For example, studies in European and North American HIV-infected cohorts report a smoking prevalence ranging from 40% to >70%, two to three times that of the general population [5][6][7][8][9][10][11]. Notwithstanding the increased prevalence of smoking, HIV-infected smokers have a significant, albeit unexplained, increased mortality and decreased quality of life compared to HIV-uninfected smokers [12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, relatively few efforts to evaluate and/or implement smoking cessation interventions for PLWH appear in the literature (Moscou-Jackson et al, 2014). Moreover, published results from randomized clinical trials (RCT) generally indicate modest long- term smoking abstinence rates and small, or no treatment group differences (Gritz et al, 2013; Humfleet et al, 2013; Lloyd-Richardson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A 2014 review of cessation interventions among persons living with HIV/AIDS indicated that these must take into account social context, mental health, and other risk behaviors. Multiple, varied interventions delivered consistently over time were most successful 20 .…”
Section: A Syndemic Approachmentioning
confidence: 99%